Chronic heart failure as a sequel of severe burn injury: first insight into a novel pathological heart-skin axis. (3rd October 2022) - Hundeshagen, G; Mertin, V; Busch, M; Thiele, P; Trogisch, F; Heineke, J; Egger, M; Buerkert, H; Van Linthout, S; Fielitz, J; Mayr, M; Kneser, U; et al.
Abstract: Research question: Our clinical research unveiled chronic heart failure with preserved ejection fraction (HFpEF) as a long-term sequel in survivors of severe pediatric burn injury due to a yet unknown molecular pathomechanism (1). Applying a standardized scald injury rat model, which is widely used in burn research, we systematically determined the pathophysiological impact of burn injury on cardiac performance to uncover systemic and molecular pathomechanisms that may cause post-burn injury HFpEF development. Methods: Male adolescent SD-rats were subjected to a 60% total body surface area (TBSA) full-thickness burn- or sham-trauma and subsequently characterized by serial transthoracic echocardiography, bulk myocardial next-generation sequencing and proteomics as well as RT-PCR, immuno-blotting (IB), histology and plasma proteomics for cardiac performance and molecular alterations, for up to 90 days (3, 7, 30 and 90d). Results: In comparison to the sham-group (SG, n=10), animals from the burn-group (BG, n=10; survival rate 100%) recapitulated typical post-burn clinical traits, such as significant loss in body weight (BG 27% less than SG at 30d, p<0.05) or skeletal muscle wasting (i.e., 27% less at 30d, p<0.05) in accord with elevated molecular atrophy markers throughout the observation period. Our focus on the heart revealed for the first-time post-burn cardiac muscle wasting (BG 22% less at 30d, p<0.05) and persistent markers of cardiac dysfunction in accord with significant histological cardiomyocyte hypotrophy (BG −8% at 30d, p<0.05) and significantly diminished left ventricular (LV) global longitudinal strain and isovolumic relaxation time in BGs, while LV-EF remained unchanged. Subsequent IB analysis uncovered diminished protein synthesis activity and diminished mTOR pathway activity in BG hearts. Weighted gene network correlation analysis i.e., from bulk myocardial NGS and clinical traits related activation of immunological and pro-fibrotic pathways in post-burn injury hearts to cardiac dysfunction in BGs. Subsequent RT-PCR and histology confirmed significant myocardial accumulation of cardio-depressive damage associated molecular patterns (i.e., S100A8 and A9) and infiltration by granulocytes (myeloperoxidase+) and monocytes (CD 68+) as well as significant LV fibrosis. Serial plasma proteomic analysis indicated elevated plasma levels i.e., of S100A8 and A9 and other heart failure markers that mirrored similar changes in human post-burn injury plasma samples. Conclusion: Here we report for the first time the development of HFpEF as a novel systemic consequence of severe burn injury in a rodent model, which prepares the ground for further mechanistic and translational studies. The initial observation of cardiac inflammation and fibrosis, which are known to negatively impact cardiac performance, may be mechanistic key findings that will guide further therapeutic studies and subsequent validation of post-burn heart failure biomarkers. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Rolf-Schwiete Stiftung